MENINGKATKAN KREATIVITAS GURU BIMBINGAN DAN KONSELING DI JAWA BARAT MELALUI MODEL PELATIHAN CLEAR IDEAS - Maryani, Ineu; Ahman, Ahman; Nurihsan, Juntika; Ilfiandra, Ilfiandra (Balai Diklat Keagamaan Bandung, 2023)
The purpose of this study is to determine whether the Clear Ideas Training Model has increased the creativity of guidance and counseling teachers. Using a mixed-method with a concurrent embedded strategy over three unior High School Guidance and Counseling teachers who served in West Bandung Regency. The research stage consists of preliminary studies and exploring the profile of creative teachers through guided group discussions, development of implicit theories of creativity, exploration of teachers' creative growth mindset, exploration of creative motivation, and trials of implementing the Clear Ideas Training Model. In the preliminary study and trial of the training model, a single case study method with ABA design was used. Research findings show that the Clear Ideas Training Model is effective for enhancing participants' creativity. This is evidenced by creative ideas’ emergence at the 'erupt' stage and the successful implementation of creative ideas in the form of innovative guidance and counseling services at the Clear stage. At the align for delivery stage, a creative product for Guidance and Counseling teachers was launched through Instagram social media under the name